Whole-lung low-dose radiation therapy (LD-RT) for non-intubated oxygen-dependent patients with COVID-19-related pneumonia receiving dexamethasone and/or remdesevir. (December 2021) - Hess, Clayton B.; Eng, Tony Y.; Nasti, Tahseen H.; Dhere, Vishal R.; Kleber, Troy J.; Switchenko, Jeffrey M.; Weinberg, Brent D.; Rouphael, Nadine; Tian, Sibo; Rudra, Soumon; Taverna, Luisa S.; Daisson, Alvaro Perez; et al.
Highlights: LD-RT reduced intubation rates from 32% to 14%, with trending significance ( p = 0.09). LDRT reduced inflammation (CRP, p = 0.02) and cardiac injury (CK, p < 0.01). Three day post LD-RT CRP decline predicted for reduced need for intubation (0% vs. 31%, p = 0.04). Post LD-RT CRP responders needed less individual and cumulative oxygen compared to controls ( p = 0.06). Prolonged hospitalizations (>3 weeks ) were fewer in CRP responders following LD-RT (0% vs. 31%, p = 0.04). Abstract: Background: Low-dose radiotherapy (LD-RT) has produced anti-inflammatory effects in both animal models and early human trials of COVID-19-related pneumonia. The role of whole-lung LD-RT within existing treatment paradigms merits further study. Methods: A phase II prospective trial studied the addition of LD-RT to standard drug treatments. Hospitalized and oxygen-dependent patients receiving dexamethasone and/or remdesevir were treated with 1.5 Gy whole-lung LD-RT and compared to a blindly-matched contemporaneous control cohort. Results: Of 40 patients evaluated, 20 received drug therapy combined with whole-lung LD-RT and 20 without LD-RT. Intubation rates were 14% with LD-RT compared to 32% without ( p = 0.09). Intubation-free survival was 77% vs. 68% ( p = 0.17). Biomarkers of inflammation (C-reactive protein, p = 0.02) and cardiac injury (creatine kinase, p < 0.01) declined following LD-RT compared to controls. Mean time febrile was 1.4 vs 3.3 days, respectively ( p = 0.14). Significant differences in clinical recovery (7.5 vs. 7 days, p = 0.37) and radiographic improvement ( p = 0.72) were not detected. On subset analysis, CRP decline following LD-RT was predictive of recovery without intubation compared to controls (0% vs. 31%, p = 0.04), freedom from prolonged hospitalizations (21+ days) (0% vs. 31%, p = 0.04), and decline in oxygenation burden (56% reduction, p = 0.06). CRP decline following 1st drug therapy was not similarly predictive of outcome in controls ( p = 0.36). Conclusions: Adding LD-RT to standard drug treatments reduced biomarkers of inflammation and cardiac injury in COVID-19 patients and may have reduced intubation. Durable CRP decline following LD-RT predicted especially favorable recovery, freedom from intubation, reduction in prolonged hospitalization, and reduced oxygenation burden. A confirmatory randomized trial is now ongoing. Clinical Trial Registration: NCT04366791.